Programa estratégico “Kinesis” para minimizar el déficit de atención hiperactiva (DAH) en alumnos del 1° y 2° de primaria en I.E del distrito de Rioja - Huaman Escuadra, Delia (2011)
The present work of investigation, was realised with purpose of experiment the proposal of the Program denominated "kinesis" that owns the propase of diminish the Deficit of Hyperactive Atenttion (TDAH) in children who suffer of this syndrome. For such reason we lead in the task of focusing our investigation; for which it has been taken like reference to all the Educativa lnstitutions (07) of the Leve! of Primary Education which they are in the scope of the jurisdiction of the district of Rioja, whose student population ascends to 927 students in its different sorts. lts started the execution of the investigation with the visit to the sections of First and the Second grade of each Educativa lnstitution, focused (22 sections), in order to find boys and girls with indications of the TDAH. For which, to discard this íncapacíty, it had to use the Test of Conners to the boys and girls with possible indicators with the help of a professional in psychology and the teacher of classroom that participated in this action. Product of this activity, was 30 children with this upheaval, which was summoned to a meeting of coordination with the parents of family (30) of these children, for the execution and their participation in the different factorías that were realised; as well as of the teachers that they have to these children in their classrooms so that they have the information .about the TDAH. Similarly, we met to the 30 children in a classroom preparad for them in the FEH-R in order to develop the factories classes types the days Saturdays anc Sundays during 1 O sessions of learning, monitored by means of the instrument of Checklist to be measuring with the advance of the factories, the degree of diminution of the TDHA in the children; which is inferred that, with the application of the proposal of the program "kinesis", lt's demonstrated the significant development of the attention of children .in front TDAH in the I.E of the district of Rioja; since when realising the statistical tests verified the obtained results product of the use of the statistical formulates (twin comparison) for the verification of the hypothesis, it obtained a value calculated of te = 21 ,34 and a tabular value of tt = 1,699 (obtained of th.e table. of probability of t distribution of Student, with a leve/ of signíficance of 5% and 29 degrees ofliberty), verifying that the ca!culated value is major that the . tabular value, which allows that the null hypothesis is located into of the region of rejection. The refore it is decided to accept the hypothesis of investigation with a level of confidence of 95%, the same that is demonstrated in the graph of the curve of Gauss. In addition we were applied the measurements of the levels of emotional upheavals, disorders conduct, difficulties in the learning in the children with this incapacity; as well as we were applied the measurements of the levels on the knowledge of the TDAH, levels of communication as much in the teachers and the parents of family .